Attitudes of tourist boards on the involvement of local people in the development of tourism in nature protected areas: the example of the Mura-Drava Regional Park - Golub, Barbara; Jaković, Božidar (Oeconomica Jadertina, 2019)
Protected areas of nature have a long history, and during this century there has been a significant increase in the number and species of them. The reason for this is an increase in awareness among people when it comes to natural values, but also the need for protection due to the exploitation of resources abundant in such areas. The beginning of tourism development in nature protected areas is related to the establishment of national parks and represents the process of connecting visitors with the natural and cultural heritage of the area being visited. It creates many benefits for the local community as well as potential costs that, if mismanaged, can have significant environmental, social and cultural consequences. For this reason, it is important to determine what tourism activities can be undertaken in such areas and to pay particular attention to sustainable development, especially when it comes to the needs of the local population. It is well known that the implementation of certain sustainable tourism tools can, among other things, encourage the active involvement of the local population in the development of tourism in protected areas, as one of the most important stakeholders in the development of tourism. Accordingly, the paper is designed to identify opportunities and forms of involvement of the local population in tourism development in nature protected areas, reasons for supporting the tourism by the local population and how they communicate with the tourist communities, with a preliminary overview of the importance of their involvement.
Keywords: sustainable tourism; local population; local community; nature protected areas; MuraDrava Regional Park